Cobalt (II) and Nickel (II) Complexes with Schiff Base Ligand Derived From 4-Amino Antipyrine: Synthesis, Spectral, Characterization and Thermal Studies - Razzaq Ibrahim Al-Faris, Ahmed; Mahdi Sachit Alkoofee, Wafaa; ., . (International Journal of Engineering and Technology, 2018)
Metal complexes of the Schiff base ligand, synthesized via condensation p-dimethylamino benzaldehyde with Bis (4-aminoantipyrine) benzene 1, 4-diamine which has synthesized from condensation 1, 4-phenylene diamine and 4-aminoantipyrine, are synthesized from chloride salts of Co (II) and Ni(II) with ligand in ethanol. The metal complexes and ligand are characterized on the basis of elemental analyses, melting point, molar conductance, UV â€“Visible, FTIR and thermogravimetric analysis. The molar conductance data reveal that the metal chelates of the ligand with Co (II) and Ni (II) are electrolytes. The present results suggested that the Schiff base ligand as tetradentate is coordinated with metal ions through the four nitrogen atoms.Â